2019
DOI: 10.14368/jdras.2019.35.3.160
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effect of toothbrush with light emitting diode on dental biofilm attached to zirconia surface: an in vitro study

Abstract: The purpose of this study was to evaluate the antimicrobial effects of a toothbrush with light-emitting diodes (LEDs) on periodontitis-associated dental biofilm attached to a zirconia surface by static and dynamic methods. Materials and Methods: Zirconia disks (12 mm diameter, 2.5 mm thickness) were inserted into a 24-well plate (static method) or inside a Center for Disease Control and Prevention (CDC) biofilm reactor (dynamic method) to form dental biofilms using Streptococcus gordonii and Fusobacterium nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Through BOMP and GI tests, we confirmed the effects of the 3-component complex LED, and these results are in concordance with our previous findings of the reduction of P. gingivalis on sand-blasted titanium disks with LED toothbrushes in vitro [ 10 ]. Furthermore, our results agree with those of another in vitro study reporting that LED toothbrushes with erythrosine reduced microorganism growth on dental biofilms attached to a zirconia surface [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Through BOMP and GI tests, we confirmed the effects of the 3-component complex LED, and these results are in concordance with our previous findings of the reduction of P. gingivalis on sand-blasted titanium disks with LED toothbrushes in vitro [ 10 ]. Furthermore, our results agree with those of another in vitro study reporting that LED toothbrushes with erythrosine reduced microorganism growth on dental biofilms attached to a zirconia surface [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
“…Since the antimicrobial activity of LEDs has been confirmed, attempts have been made to combine toothbrushes with LEDs. We recently observed that in vitro , erythrosine-treated LED toothbrushes efficiently diminished the number of Porphyromonas gingivalis cells attached to titanium and zirconia surfaces compared to a commercial photodynamic treatment kit [ 10 11 ]. Additionally, Lee [ 12 ] reported that an LED electric toothbrush was an effective tool for patients with gingivitis based on results from 4 weeks of use.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of supporting bone around an implant is what causes peri‐implantitis, an irreversible inflammatory reaction [95]. According to Park et al [101], LEDs are effective in inhibiting the growth of periodontal biofilms connected to zirconia surfaces, including stress‐inducing bacteria like F. nucleatum and Streptococcus gordonii , which can cause periodontitis. Zirconia‐attached periodontitis‐associated bacteria are less likely to survive after brushing with an LED toothbrush that contains erythrosine than after using other treatments [101].…”
Section: The Antimicrobial Effect Of Photodynamic Therapymentioning
confidence: 99%
“…According to Park et al [101], LEDs are effective in inhibiting the growth of periodontal biofilms connected to zirconia surfaces, including stress‐inducing bacteria like F. nucleatum and Streptococcus gordonii , which can cause periodontitis. Zirconia‐attached periodontitis‐associated bacteria are less likely to survive after brushing with an LED toothbrush that contains erythrosine than after using other treatments [101]. Graphene nano‐platelets coated on titanium surfaces were found to have antimicrobial properties.…”
Section: The Antimicrobial Effect Of Photodynamic Therapymentioning
confidence: 99%
“…Since light-emitting diode (LED) showed the antimicrobial effects (56,57), it has been recently applied to toothbrushes in order to enhance the efficacy in reducing dental plaque and improve gingival health. The in vitro studies demonstrated that the LED toothbrushes were able to reduce the number of Porphyromonas gingivalis attached to titanium and zirconia surfaces (58,59). In 2015, a pilot clinical study by Genina et al found that the blue LED toothbrushes with 412 nm wavelength significantly reduce dental plaque, gingival bleeding, and inflammation more than the manual toothbrushes (18).…”
Section: Light-emitting Diode (Led) Toothbrushesmentioning
confidence: 99%